2012
DOI: 10.1653/024.095.0335
|View full text |Cite
|
Sign up to set email alerts
|

Brachymeriaspp. (Hymenoptera: Chalcididae) Parasitizing Pupae of Hersperidae and Nymphalidae (Lepidoptera) Pests of Oil Palm in the Brazilian Amazonian Region

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…There are some records of Brachymeria spp. parasitising directly Lepidoptera pupae, such as Nymphalidae Tavares 2005, 2006;Nardi et al 2006;Tinôco et al 2012;Santos-Murgas et al 2019), Geometridae (Zache et al 2012), Saturniidae (Ramírez et al 2004), and Hesperiidae around Indonesia, India, Panama, and North and South Regions of Brazil (Salgado-Neto et al 2010;Erniwati and Ubaidillah 2011;Tinôco et al 2012;Gupta and Kalesh 2012;Gupta et al 2016;Santos-Murgas et al 2021;James et al 2022). The only information in respect of parasitism of Cynea is a report of the braconid Alphomelon xestopyga Deans, 2003 on larvae of C. irma (Janzen and Hallwachs 2009).…”
Section: Resultsmentioning
confidence: 99%
“…There are some records of Brachymeria spp. parasitising directly Lepidoptera pupae, such as Nymphalidae Tavares 2005, 2006;Nardi et al 2006;Tinôco et al 2012;Santos-Murgas et al 2019), Geometridae (Zache et al 2012), Saturniidae (Ramírez et al 2004), and Hesperiidae around Indonesia, India, Panama, and North and South Regions of Brazil (Salgado-Neto et al 2010;Erniwati and Ubaidillah 2011;Tinôco et al 2012;Gupta and Kalesh 2012;Gupta et al 2016;Santos-Murgas et al 2021;James et al 2022). The only information in respect of parasitism of Cynea is a report of the braconid Alphomelon xestopyga Deans, 2003 on larvae of C. irma (Janzen and Hallwachs 2009).…”
Section: Resultsmentioning
confidence: 99%
“…The natural biological control agents in palm tree crop in Brazil includes Chalcididae (Hymenoptera), Tachinidae and Sarcophagidae (Diptera) parasitizing Brassolis astyra Godart, B. sophorae, O. invirae and Opsiphanes sp. (Lepidoptera: Nymphalidae) larvae and pupae in the coconut (Cocus nucifera) (Marcicano et al, 2007(Marcicano et al, , 2009 and oil palm (E. guineensis) (Tinôco et al, 2012) culture. This shows the importance of manipulating natural enemies to increase the biological control (Dobbs and Potter, 2016;Pereira et al, 2015;Smith et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…scutellaris, were identified as B. koehleri (Figure 1B). In Brazil, B. koehleri was reported as a hyperparasitoid of C. scutellaris through Opsiphanes invirae (Huebner, 1818) (Lepidoptera: Nymphalidae), in Pará (Tinôco et al, 2012) and was also reported as a hyperparasitoid of Lespesia melloi (Gil-Santana, Nihei & Nunez, 2014) (Diptera: Tachinidae) through pupae of Thagona tibialis Walker, 1855 (Lepidoptera: Lymantriidae) (Tavares et al, 2013), in Lespesia sp. (Diptera: Tachinidae) through pupae of Parides ascanius (Cramer, 1775) (Lepidoptera: Papilionidae) in Rio de Janeiro, Brazil (Tavares et al, 2006).…”
mentioning
confidence: 99%